Patient Voice in Rare Disease Drug Development and Endpoints. (March 2017) - Deal, Linda S.; Goldsmith, Jonathan C.; Martin, Susan; Barbier, Ann J.; Roberds, Steven L.; Schubert, David H.
While planning for a successful clinical trial in a prevalent condition is no trivial orchestration, even more complicated is the coordination of novel, delicate and critical operational components necessary for the successful conduct of clinical trials of rare disease (RD). We highlight some of the inherent and practical challenges to conducting clinical trials and selecting or developing endpoints for RD and the importance of including the patient voice or perspective. These challenges include the lack of regulatory precedent for proposed endpoints, a void of available measures, little or no published literature or natural history information, the practicalities of obtaining access to patients, and the appropriateness of placebo-controlled trials. As part of our review, we include practical considerations for addressing these issues along with a regulatory perspective regarding potential logistic and methodologic challenges. We conclude that the patient perspective is a critical component in defining treatment benefit and in interpreting the meaningfulness of a change (or lack thereof). Engaging with patients is needed at multiple steps along the long road of drug discovery.